Use of Self-Massage Techniques in Speech Therapy Practice - Ishmatova Ozoda Sirozhiddinovna (PT. Pusmedia Group Indonesia, 2025)
Background: Speech disorders affect 15-20% of children, requiring comprehensive interventions. Self-massage represents a promising cost-effective adjuvant technique that may enhance therapy outcomes through proprioceptive stimulation and muscle tone normalization. Objective: To evaluate self-massage effectiveness as an adjuvant technique in pediatric speech therapy for children with speech disorders. Methods: A quasi-experimental study involved 36 children aged 4-7 years with dysarthria (n=12), stuttering (n=12), and phonetic-phonemic perception disorders (n=12). Participants performed structured self-massage targeting head-neck, facial, and tongue muscles twice daily for 5-10 minutes over four weeks. Assessments included articulation, speech motor skills, fluency, and communication confidence at baseline, 2, 4, and 8 weeks. Results: All groups showed significant improvements. Dysarthria group demonstrated enhanced articulation and speech motor coordination. Stuttering group exhibited reduced disfluency and improved speech rhythm. Phonetic-phonemic disorder group showed normalized perception and improved speech production. Communication confidence increased across all groups with high compliance rates (>90%). Conclusions: Self-massage proved effective as an adjuvant pediatric speech therapy technique, improving speech motor function, articulation, and psychological well-being with high feasibility as a home-based program. This study contributes evidence-based framework for integrating accessible, cost-effective interventions in speech therapy practice. Future randomized controlled trials with larger samples, longer follow-up periods, and neuroimaging studies to explore underlying mechanisms are recommended.